When Small Bugs Cause Big Problems: Tropical Insect Bite Led to Myocarditis - Habib, SM Ahsanul; Mohammad, Taneem; Alam, Mohammad Ashraful (Community Based Medical Journal, 2023)
Wasp bite induced allergic reactions or organ dysfunctions are not uncommon in tropical countries. Most people affected with insect bite hardly develop any signs or symptoms; however, about 30 percent of them may show signs of illness which is often overlooked and causes fatality. Among the fatal complications specially anaphylaxis and renal dysfunction have been reported; however, myocardial involvement in the form of myocarditis is very rare. Awareness about such complications is important as these affect the clinical course and outcomes of the patients. We have presented a case of wasp bite induced myocarditis and heart failure here, which was diagnosed at a later stage as patient did not improve being admitted in the emergency department and subsequently transferred to the critical care unit. CBMJ 2023 January: Vol. 12 No. 01 P: 107-110